1988
DOI: 10.1159/000293706
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Differences in Immunohistochemical Localization of New Placental Proteins (PP1, PP19, PP21) in the Human Placenta

Abstract: The immunohistochemical localization in the human placenta of new placental proteins PP1, PP19, and PP21 was clarified using modified indirect enzyme-labeled antibody method and compared with that of pregnancy-specific Β1-protein (SPl). The major results are as follows: positive staining for PP1 was seen at the nucleus and cytoplasm of villous cytotrophoblasts, the X cells at the basal plate, and of chorionic trophoblasts, while the decidua cells and amnion were not stained. PP19 was characteristica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1989
1989
1992
1992

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The higher PP19 concentration in the chorionic villous trophoblast compared to the decidua, chorion, and amnion, coincides with immunohistochemical findings that PP19 localization in the human placenta was marked in the chorionic villous syncytiotrophoblast but little in the amnion [2].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The higher PP19 concentration in the chorionic villous trophoblast compared to the decidua, chorion, and amnion, coincides with immunohistochemical findings that PP19 localization in the human placenta was marked in the chorionic villous syncytiotrophoblast but little in the amnion [2].…”
Section: Discussionsupporting
confidence: 84%
“…In a previous study [2], we demonstrated an unique localization of PP19 in the human placenta, that is, an immunoreactive staining for PP19 seen in the villous syncytiotrophoblast, the X-cell at the basal plate, and the chorionic trophoblast. Characteristically staining in these cells was more prominent at the nucleus than at the cytoplasm.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations